Model Formulasi dan Pengendalian Mutu Berkelanjutan Food Grade Grease Berbasis Sumber Daya Agroindustri untuk Mendukung Keamanan dan Kehalalan Produk Pangan - Nina Hairiyah; Nuryati; Raden Rizki Amalia; Fatimah; Imron Musthofa (Universitas Djuanda, 2026)
Food safety and halal assurance of food products are influenced not only by the primary food ingredients but also by processing aids, one of which is food grade grease used in food processing equipment. Dependence on imported products and the lack of integration between formulation and process-based quality control highlight the need for the development of a sustainable scientific model based on local agroindustry resources. This study aims to develop a sustainable formulation and quality control model for agroindustry-based food grade grease to support food safety and halal assurance. The study employed a fundamental research approach, with food grade grease as a case study for model development. The research stages included the identification of Critical Quality Characteristics (CQC), selection and physicochemical characterization of agroindustry-based materials, formulation design using Design of Experiment (DOE), and the application of Statistical Quality Control (SQC) to analyze process stability and capability. The results indicate that the developed formulation model successfully identified quantitative relationships between material composition and critical quality parameters, with product quality consistency maintained within statistical control limits. The implementation of SQC demonstrated that the formulation process was stable, with process capability indices (Cp and Cpk) greater than 1.33 for key quality parameters. The integration of formulation and quality control models produced a conceptual framework capable of mapping critical quality points, process variability, and sustainability indicators, including resource-use efficiency and potential agroindustrial waste reduction. The proposed model is expected to serve as a scientific reference for the development and quality supervision of food processing aids that support food safety, halal assurance, and sustainable agroindustry principles.